Changes in fatty acids, vitamins, cholesterol and amino acid profiles of ram semen by freeze-thawing process - Gungor, Ibrahim Halil; Koca, Recep Hakki; Cinkara, Serap Dayan; Acisu, Tutku Can; Erisir, Figen Erdem; Arkali, Gozde; Turk, Gaffari (Elsevier, 2025)
The objective of this study was to examine the impact of freeze-thawing on the levels of oxidative stress, fatty acids, vitamins A, D, E, and K, cholesterol, and amino acids, as well as on spermatological parameters, in ram semen. Semen was collected and pooled from each of the seven rams twice a week for three weeks. The mixed semen was diluted with tris + egg yolk diluent at 38 degrees C (Group 38 degrees C) and the temperature was reduced to 5 degrees C (Group 5 degrees C). Following the glycerolization-equilibration process (Group G-E), the samples were automatically frozen in liquid nitrogen vapor at -140 degrees C. The semen samples were thawed 24 h after freezing (Group FrozenThawed, F-T). A comparison of Group 38 degrees C with Group F-T revealed significant differences in several parameters. Motility rates, kinematic values, percentage of membrane integrity (HOS), some PUFA levels, & sum;SFA and amino acid levels were significantly lower in Group F-T. Conversely, the ratio of dead and static spermatozoa, lipid peroxidation level, some PUFA levels, & sum;MUFA, vitamins A, E and cholesterol levels were significantly higher in Group F-T. The majority of these alterations were also evident in semen samples subjected to G-E treatment. In conclusion, exposure of ram semen to G-E and F-T treatments results in modifications to semen, fatty acid, vitamin, and amino acid profiles, accompanied by elevated levels of lipid peroxidation. Moreover, this study demonstrated, for the first time, that oxidative stress was induced, some amino acid levels were altered, vitamin A and E levels were increased, vitamin D and K levels were not affected, and beta-sitosterol levels were decreased after freeze-thawing in ram semen.
Keywords: Amino acids; Lipids; Freeze-thawing; Ram semen; Vitamins